Research status and hotspots of oncology genetic nursing: a bibliometric analysis - Hu, Ya; Fu, Cangmei (Frontiers in Oncology, 2025)
BackgroundCancer is a major global challenge in the 21st century, posing significant social, public health, and economic pressures. Not only does it shorten human lifespans, but it also imposes substantial burdens on society and the macroeconomy. Oncology genetics nursing specialty focuses on providing genetic testing, genomic analysis, and related services to patients. Due to the growing demand for cancer risk assessment, widespread genetic testing, and increasing rates of hereditary cancers, the need for genetic counseling has grown exponentially. To our knowledge, no comprehensive bibliometric study has yet been conducted to systematically compile relevant data in this field.ObjectiveThis study attempts to review existing literature in the field of oncology genetic nursing, highlight current hot topics, and predict future development trends.MethodsA bibliometric analysis was conducted by searching relevant literature on oncology genetic nursing from January 1, 1999 to August 6th, 2025 in the Web of Science Core Collection (WOSCC). The CiteSpace software was used to map publication volume, country and author collaboration networks, keyword co-occurrences, and word emergence.ResultsThe study analyzed 658 articles from January 1, 1999 to August 6th, 2025. The United States leads in cooperative publications in oncology genetic nursing, with 407 of total publications, including the top 10 institutions, most published authors (N=28), and most cited authors (N=47). Breast cancer (N=146), ovarian cancer (N=40) and colorectal cancer (N=25) are the main diseases studied. Primary research hotspots include offering nurse-led genetic risk assessments, genetic testing, and genetic counseling services, as well as improving the training of senior oncology genetic practice nurses. Emerging trends focus on genetic testing, genetic counseling and precision medicine in oncology genetic nursing.ConclusionThis bibliometric study maps the research hotspots and trends for the past more than 26 years  in oncology genetic nursing. Our findings will enable researchers to better understand trends in this field and find suitable directions and partners for future research.